Effects of Interaction between Dual Shaking Tables and Specimen and Force Feedback Compensation Control - Fangfang Li; Xiaojun Li; Juke Wang (Shock and Vibration)
The shaking table array system is composed of multiple shaking tables for seismic response simulation tests of large-span spatial structures, bridge structures, slender structures such as pipeline and aqueduct, complex structures, and so on. In the process of testing with the multiple shaking tables, the interaction between the shaking tables and specimen affects the output accuracy of the shaking tables. The characteristics and rules of the dual shaking tables-specimen interaction effects on the system performance were analyzed in this paper. In order to improve the output accuracy of the dual shaking tables, force feedback compensation was introduced into three-variable control to reduce the interaction effects. However, the measurement errors of the force in the actuator and the acceleration of the shaking tables existed in the process of force feedback compensation. In order to verify the effectiveness of force feedback compensation for interaction between the dual shaking tables and specimen, the error influences on the system performance were simulated.